Learn by Doing: An Academic Integrity Policy Revision - Seeland, Josh; Munn, Caitlin (Canadian Perspectives on Academic Integrity, 2021)
After several years of developing a culture of academic integrity at Assiniboine Community College, over twenty stakeholders from five college campuses and a dozen different service areas and academic programs formed the Academic Integrity Advisory Committee (AIAC) in late 2019. In the midst of a push through emergency remote learning, and towards blended learning ahead, they undertook a multi-stage plan: to develop, implement, and evaluate a revised academic integrity policy. Using research and evidence from the world’s foremost sources to inform their work, the AIAC embodied Assiniboine’s academic signature of learn by doing. Join members of the AIAC for a detailed look at the ins and outs of this policy revision process. Participants will leave this session with an understanding of several key academic integrity frameworks, how to implement a change model at their own institution, and a deeper understanding of how to collaboratively develop an academic integrity policy.